Sistem Fogging Spray Machine Disinfektan Berbasis Remote Control Dan Microkontroler Arduino - Juliantara, Roziardi Putra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Environmental health needs to be a major concern, such as air pollution which results in environmental pollution. That currently 90% of humans do their activities in closed spaces. Air cleanliness in closed spaces is important because it has a direct impact on human health. The aim of this research is to design a Remote Control and Microcontroller Based Disinfectant Fogging Spray Machine System. This tool will use Arduino – Nano as a Microcontroller and Remote Control as a driver and a Wireless IP Camera to monitor the work tool. This tool will require an NRF24L01 PA LNA 2.4Ghz as a detector signal transmitter at a distance of 10cm, an Oled LCD as an output and a GY - 906 temperature sensor that will measure the voltage and temperature that will be used by the tool. Testing CCTV cameras by controlling the Smartphone to find out the distance of the object to be sprayed. And controlling the tool via smartphone, to avoid dangerous areas. The Disinfectant Fogging System uses a CCTV camera system so that it can detect the distance to be sprayed and the cellphone will display an image or video. The remote control will hold or direct what will be sprayed, so that the disinfectant machine will release disinfectant fogging spray liquid.